Effects of the Natural Environment on the Subjective and Psychological Well-Being of Older People in the Community in China - Kangcheng Gong; Chendi Wang; Jun Yin (Buildings)
As people age, their activity radius gradually narrows, leading to increased interaction with the community environment. The natural environment (NE) within the community may influence the subjective and psychological well-being (SPWB) of older people (i.e., air quality, noise, green space, and blue space). To enhance the NE and promote the SPWB of older people, this study explored the effect of the community NE on the SPWB of older people. A questionnaire survey involving 180 older people from three communities was collected, alongside observations and measurements of the NE within the community. Finally, a NE-SPWB model was established, indicating that smell (air), ambient noise, green space areas, water landscapes, and smell (water) all positively influenced the SPWB of older people. Based on these findings, recommendations were proposed to enhance community environmental conditions, such as improving water landscapes and green spaces, to further enhance the well-being of older people.